2021
DOI: 10.1021/acsnano.1c07739
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Functionalization and Emergence of Long-Range Spin-Dependent Phenomena in Two-Dimensional Carbon Nanotube Networks

Abstract: Molecular functionalization of CNTs is a routine procedure in the field of nanotechnology. However, whether and how these molecules affect the spin polarization of the charge carriers in CNTs are largely unknown. In this work we demonstrate that spin polarization can indeed be induced in two-dimensional (2D) CNT networks by “certain” molecules and the spin signal routinely survives length scales significantly exceeding 1 μm. This result effectively connects the area of molecular spintronics with that of carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 59 publications
2
32
0
Order By: Relevance
“…Another area of increasing interest in which these hybrid hydrogels can find useful applications is the area of organic or molecular spintronics . This area studies spin transport through organic compounds or materials and has shown that there is a connection between the chirality of the molecule and the spin polarization, named the CISS effect. Organic molecules, in general, have poor electronic conductivity, which limits their potential device applications.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Another area of increasing interest in which these hybrid hydrogels can find useful applications is the area of organic or molecular spintronics . This area studies spin transport through organic compounds or materials and has shown that there is a connection between the chirality of the molecule and the spin polarization, named the CISS effect. Organic molecules, in general, have poor electronic conductivity, which limits their potential device applications.…”
mentioning
confidence: 99%
“…Given the immense technological importance of CNTs in the areas of electronic devices, circuits, and sensors, such functionalities could allow the development of a wide range of spintronic devices. Initial studies in this direction have employed single-strand DNA and peptides and have shown a correlation between the nanotube–molecule interaction strength and the observed CISS effect. , The induced spin polarization also affects carrier transport in nanotubes via spin-momentum locking, which is a signature property of CISS …”
mentioning
confidence: 99%
See 3 more Smart Citations